2022
DOI: 10.3390/electronics11244100
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fruit Maturity, Quality, and Its Life Using Deep Learning Algorithms

Abstract: Fruit that has reached maturity is ready to be harvested. The prediction of fruit maturity and quality is important not only for farmers or the food industry but also for small retail stores and supermarkets where fruits are sold and purchased. Fruit maturity classification is the process by which fruits are classified according to their maturity in their life cycle. Nowadays, deep learning (DL) has been applied in many applications of smart agriculture such as water and soil management, crop planting, crop di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Handayanto et al [14] used color and texture features of bananas to classify their maturity through a neural network model with a discrimination accuracy of 95.24%. Aherwadi et al [15] trained and validated the maturity of bananas using both CNN and AlexNet models, and further classified unripe, ripe, and overripe bananas accurately. The results showed that both models had an accuracy rate of over 98% in predicting the maturity of bananas.…”
Section: Detection Of Maturity Levelmentioning
confidence: 99%
“…Handayanto et al [14] used color and texture features of bananas to classify their maturity through a neural network model with a discrimination accuracy of 95.24%. Aherwadi et al [15] trained and validated the maturity of bananas using both CNN and AlexNet models, and further classified unripe, ripe, and overripe bananas accurately. The results showed that both models had an accuracy rate of over 98% in predicting the maturity of bananas.…”
Section: Detection Of Maturity Levelmentioning
confidence: 99%
“…|𝑌 𝐹𝑀 (𝑡) − 𝑟𝑙. 𝑃𝑟𝑒𝑦(𝑡) (11) where t is the present repetition, 𝑌 𝑀 (𝑡) indicates jackal, 𝑌 𝐹𝑀 (𝑡) designates the site of the female, besides Prey(t) is the site prey. 𝑌 1 (𝑡) and 𝑌 2 (𝑡) are the female and male golden jackals' most recent locations.…”
Section: Golden Jackal Optimization Algorithm For Fine-tuningmentioning
confidence: 99%
“…where 𝐸 0 is a random sum in the range [-1, 1], representing the prey's initial energy; T characterizes the maximum sum of repetitions; c1 is the default continuous set to 1.5; and 𝐸 1 energy In Equations ( 10) and (11), |Y M (t) − rl • Prey(t)| designates the distance among the golden jackal and prey besides "rl" is the vector of random statistics intended by the Levy flight function. 𝑟𝑙 = 0.05.…”
Section: Golden Jackal Optimization Algorithm For Fine-tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…The AI algorithms can be trained using a large dataset of images of different fruits with varying quality. They can learn to identify the specific features that indicate the quality of the fruit [6].…”
Section: Introductionmentioning
confidence: 99%